The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jacc.2020.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings in Pediatric Multisystem Inflammatory Syndrome Associated With COVID-19 in the United States

Abstract: Background Centers from Europe and United States have reported an exceedingly high number of children with a severe inflammatory syndrome in the setting of COVID-19, which has been termed multisystem inflammatory syndrome in children (MIS-C). Objectives This study aimed to analyze echocardiographic manifestations in MIS-C. Methods We retrospectively reviewed 28 MIS-C, 20 healthy controls and 20 classic Kawasaki disease (KD) patients. We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
267
12
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(332 citation statements)
references
References 31 publications
46
267
12
7
Order By: Relevance
“…Respiratory status was not significantly impacted in any patients included in our study, or in most of the literature reports of children with MIS-C, which describe similar incidence of MV than us, and mostly used in the context of shock for hemodynamic stabilization. 9,10,13,18 This finding contrasts with those of studies of adults 49 and with the report by Sun et al and Shekerdemian et al 6,8 in children with COVID-19 (not diagnosed with MIS-C), in whom the primary reason for PICU admission was respiratory distress. In our series, the 2 patients that required MV for stabilization showed mild to moderate respiratory distress, both had signs of fluid overload and atelectasis as evidenced on chest X-ray, and improved soon after the treatment was optimized.…”
Section: Respiratory Involvementcontrasting
confidence: 70%
See 4 more Smart Citations
“…Respiratory status was not significantly impacted in any patients included in our study, or in most of the literature reports of children with MIS-C, which describe similar incidence of MV than us, and mostly used in the context of shock for hemodynamic stabilization. 9,10,13,18 This finding contrasts with those of studies of adults 49 and with the report by Sun et al and Shekerdemian et al 6,8 in children with COVID-19 (not diagnosed with MIS-C), in whom the primary reason for PICU admission was respiratory distress. In our series, the 2 patients that required MV for stabilization showed mild to moderate respiratory distress, both had signs of fluid overload and atelectasis as evidenced on chest X-ray, and improved soon after the treatment was optimized.…”
Section: Respiratory Involvementcontrasting
confidence: 70%
“…32,33 Considering this, the increased inflammatory markers in our patients, and previous experience in adults with severe COVID-19, all received immunomodulatory drugs. This pattern of increased inflammatory markers has also been reported in most of the case series studies of children with MIS-C. [9][10][11][12][13]17,18 It has been reported that low-dose steroids might be beneficial for severe COVID-19, although this claim remains controversial. 34,35 Recently, a big randomized study from the RECOVERY collaborative group, reported preliminary results suggesting that dexamethasone reduces the 28-days mortality in adults with severe COVID-19 requiring hospitalization, mechanical ventilation or supplemental oxygen.…”
Section: Immunomodulation Therapiessupporting
confidence: 68%
See 3 more Smart Citations